A Plant Bioreactor for the Synthesis of Carbon Nanotube Bionic Nanocomposites - Magnabosco, Giulia; Pantano, Maria F.; Rapino, Stefania; Di Giosia, Matteo; Valle, Francesco; Taxis, Ludovic; Sparla, Francesca; Falini, Giuseppe; Pugno, Nicola M.; Calvaresi, Matteo (Frontiers in Bioengineering and Biotechnology, 2020)
Bionic composites are an emerging class of materials produced exploiting living organisms as reactors to include synthetic functional materials in their native and highly performing structures. In this work, single wall carboxylated carbon nanotubes (SWCNT-COOH) were incorporated within the roots of living plants of Arabidopsis thaliana. This biogenic synthetic route produced a bionic composite material made of root components and SWCNT-COOH. The synthesis was possible exploiting the transport processes existing in the plant roots. SECM measurements showed that SWCNT-COOH entered the vascular bundles of A. thaliana roots localizing within xylem vessels. SWCNT-COOH preserved their electrical properties when embedded inside the root matrix, both at a microscopic and macroscopic level, and did not significantly affect the mechanical properties of A. thaliana roots.